ON INTEGRAL LOGARITHMIC MEANS OF BLASCHKE PRODUCTS FOR A HALF-PLANE - Mikayelyan, G.V.; Hayrapetyan, F.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
Using the Fourier transforms method for meromorphic functions we characterize the behavior of the integral logarithmic mean of arbitrary order of Blaschke products for the half-plane.